Learning to Live with Crime : American Crime Narrative in the Neoconservative Turn - Wilson, Christopher P. (Christopher Pierce), 1952- (Book collections on Project MUSE., 2010)
"In Learning to Live with Crime, Christopher P. Wilson examines this war on crime and how it has made its way into cultural representation and public consciousness. Under the sway of neoconservative approaches to criminal justice and public safety, Americans have been urged to see crime as an inevitable risk of modern living and to accept ever more aggressive approaches to policing, private security, and punishment. The idea has been not simply to fight crime but to manage its risks; to inculcate personal vigilance in citizens; and to incorporate criminals' knowledge through informants and intelligence gathering. At its most scandalous, this study suggests, contemporary law enforcement has even come to mimic crime's own operations"--Publisher's description.